SYSTEMIC MANAGEMENT IN A TRANSFORMING ECONOMУ - G. B. Kleiner (Стратегические решения и риск-менеджмент)
The paper classifies kinds of management and shows that in terms of transforming economy systemic management, focused on the development of basic economic systems and their stable complexes, is the most relevant.